Optimizing Muza-Smoked Salted Egg Production: A SWOT Analysis of an Empowerment Program Leveraging the Triple Helix Model - Novandinata, Suwigda Agung; Azizah, Siti; Manab, Abdul; Djunaidi, Irfan H; Rachmawati, Achadiah; Indrati, Rositawati; Rinanti, Rosyida Fajri (Jurnal Ilmu-Ilmu Peternakan, 2024)
Efforts to improve the quality of small and microenterprises (SMEs) depend not only on the availability of internal resources but also on innovation and worldwide regulation dynamics. The triple helix concept has become an alternative solution for improving the quality of SMEs, which consists of academicians, governments, and businesses (SMEs). Muza is an SME that is being fostered by lecturers in the Faculty of Animal Science Universitas Brawijaya in Blitar District; this SME produces smoked salted eggs and has become one of the featured products based on Blitar's Service of Fishery and Livestock Department. The communication between the academician and the Muza Management-Government on the development program was implemented separately. This research aimed to develop development strategies to increase the quality of Muza smoked salted eggs. The research was conducted in Blitar District in July 2022. The research used an explanatory method to identify problems in the field and categorize the problems into groups using the SWOT method. SWOT components are formed using in-depth interviews with the planner and implementer of the strategy, which consists of five people. The subjects were given a closed questionnaire that consisted of SWOT components. The SWOT analysis results show that the total IFE score is 4 and the EFE score is 4.45. The IE matrix shows that the empowerment strategy is on the “V” cell, which has a "hold and maintain" strategy. Thus, the programs given were not efficient, and strategic planners need to focus on product quality improvement. The design of GMP and HACCP systems is strongly recommended.